Databook of adhesion promoters - Wypych, Anna (ChemTec Publishing, 2018)
Databook of Adhesion Promoters contains data on the most important adhesion promoter products in use today. The information on each adhesion promoter is divided into five sections: General Information, Physical Properties, Health and Safety, Ecological Properties, and Use and Performance. This databook is an extremely useful source of data for engineers, technicians and researchers involved in development, manufacture, legislation or the production of a variety of products. Adhesion promoters form a very important group of additives without which many industrial products cannot perform according to requirements. Silanes originally formed the most widely used group of adhesion promoters, but increasing numbers of new additives have been entering the market, increasing the options and possibilities. These additives are needed for a variety of products in which silanes do not function or are too expensive, or where better performance can be achieved with the new additive.